Alkyl Chain Length Effects of Polymer Donors on the Morphology and Device Performance of Polymer Solar Cells with Different Acceptors. Issue 30 (9th July 2019) - Pang, Shuting; Zhang, Ruiwen; Duan, Chunhui; Zhang, Song; Gu, Xiaodan; Liu, Xi; Huang, Fei; Cao, Yong
Abstract: The development of nonfullerene acceptors has brought polymer solar cells into a new era. Maximizing the performance of nonfullerene solar cells needs appropriate polymer donors that match with the acceptors in both electrical and morphological properties. So far, the design rationales for polymer donors are mainly borrowed from fullerene‐based solar cells, which are not necessarily applicable to nonfullerene solar cells. In this work, the influence of side chain length of polymer donors based on a set of random terpolymers PTAZ‐TPD10‐C n on the device performance of polymer solar cells is investigated with three different acceptor materials, i.e., a fullerene acceptor [70]PCBM, a polymer acceptor N2200, and a fused‐ring molecular acceptor ITIC. Shortening the side chains of polymer donors improves the device performance of [70]PCBM‐based devices, but deteriorates the N2200‐ and ITIC‐based devices. Morphology studies unveil that the miscibility between donor and acceptor in blend films depends on the side chain length of polymer donors. Upon shortening the side chains of the polymer donors, the miscibility between the donor and acceptor increases for the [70]PCBM‐based blends, but decreases for the N2200‐ and ITIC‐based blends. These findings provide new guidelines for the development of polymer donors to match with emerging nonfullerene acceptors. Abstract : The side chain length of polymer donors can lead to miscibility differences. Shortening the side chains of polymer donors improves the device performance of fullerene‐based solar cells, but deteriorates the performance of small molecular and polymeric nonfullerene solar cells. Morphology investigations unveil that the miscibility between donor and acceptor in blend films depends on the side chain length of polymer donors.